Propriedades tecnológicas da madeira de Tectona grandis L.f. proveniente do Vale do Rio Doce, Minas Gerais - Motta, Javan Pereira (2011)
The objective of this study was to determine the technological properties of teak (Tectona grandis L.f.) trees with 15 years old from the Vale do Rio Doce, Minas Gerais, State Brazil. The characterization of teak wood was through the anatomical description, determination of physical properties and mechanical behavior study of wood adhesion, resistance assessment of natural wood from pith to sapwood, the wood decay organisms (fungi and termites) in terms of laboratory testing with rapid decay and subterranean termite feeding preference, and studies of moisture sorption in wood. Concerning the anatomical description, the general characteristics, gross and microscopic evaluated for teak were similar to those determined by other authors for the same species and the direct relation of age with increasing fiber length and wall thickness were found. The average density was classified as moderately heavy, medium dimensional stability, and with little influence of moisture content in wood strength values. A teak wood obtained satisfactory results in the adhesion assays. The heartwood of teak was classified as resistant to wood decay organisms. The determination of sorption curves and the fit of equations for determining the equilibrium moisture content at different relative humidity is a source of information for determining the behavior of wood during the drying process and planning of drying the most appropriate species